2009
DOI: 10.1016/j.joca.2008.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucosamine sulphate on joint space narrowing, pain and function in patients with hip osteoarthritis; subgroup analyses of a randomized controlled trial

Abstract: GS was not significantly better than placebo in reducing symptoms and progression of hip OA in subgroups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…those with a K-L score of the hip ≥ 2 and a VAS pain score ≥ 30, participating in the GOAL study [22]. This showed they had a mean VAS score of 56.4 with an SD of 19.3, a mean WOMAC pain score of 51.2 with a SD of 16.4; these data are very similar to the SDs in the study of Qvistgaard et al Therefore, in the planned trial, we will include 135 patients, anticipating only 5% loss to follow-up based on the relatively short follow-up and earlier experience with loss to follow-up [22,23]. …”
Section: Methodsmentioning
confidence: 67%
“…those with a K-L score of the hip ≥ 2 and a VAS pain score ≥ 30, participating in the GOAL study [22]. This showed they had a mean VAS score of 56.4 with an SD of 19.3, a mean WOMAC pain score of 51.2 with a SD of 16.4; these data are very similar to the SDs in the study of Qvistgaard et al Therefore, in the planned trial, we will include 135 patients, anticipating only 5% loss to follow-up based on the relatively short follow-up and earlier experience with loss to follow-up [22,23]. …”
Section: Methodsmentioning
confidence: 67%
“…Non-pharmacological treatments: Self-Management Education Programs "SMEPs", self-education and life style modification: weight loss, rest and low impact aerobic fitness exercises recommended by the American Association of Orthopedic Surgeons "AAOS" [1], use of shock-absorbing shoes with insoles and mechanical support devices. These conservative measures can provide an average of 20% more pain relief when compared to NSAIDs alone in patients with OA [2].…”
Section: Non-pharmacological Treatmentsmentioning
confidence: 99%
“…Another study revealed no significant difference in rate of joint space narrowing between the two groups, and reported no case could be made for a disease-modifying effect of corticosteroids injections [1,9].…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruyere et al (2008) now report that at a mean of 5 years after cessation of the 2-3 years RCT of the sulphate that total knee replacement had been needed twice as often (19 of 131) in those who had received placebo than those who had received the sulphate (9 of 144). Rozendaal et al (2009) have now reported a 2-year study of 222 patients with hip osteoarthritis taking glucosamine sulphate. They did not find that it was significantly better than placebo in reducing symptoms or in radiographic progression of hip osteoarthritis.…”
mentioning
confidence: 99%